Absolute bioavailability and pharmacokinetics of the angiotensin II receptor antagonist fimasartan in healthy subjects. (24th December 2015) - Ghim, Jong‐Lyul; Paik, Soo Heui; Hasanuzzaman, M.; Chi, Yong Ha; Choi, Hyang‐Ki; Kim, Dong‐Hyun; Shin, Jae‐Gook
Abstract: The present study was conducted to determine the absolute bioavailability of fimasartan (FMS; Kanarb ® ) after the single oral administration of a 60‐mg tablet or a single 30‐mg intravenous (IV) infusion. This investigation was a randomized, single‐dose, open‐labeled, two‐way crossover study of 16 healthy Korean male subjects. The subjects were divided into two groups (n = 8) and each received either the oral or IV formulation followed by one‐week washout period. The Cmax (ng/ml) and AUC∞ (h · ng/ml) following oral and IV administration were 62.4 ± 48.6 and 291.1 ± 121.7; and 683.3 ± 104.3 and 782.3 ± 112.7 (mean ± SD), respectively. The Tmax (h) were 3.0 h (range: 0.5–5.0 h) and 1.0 h (range: 0.8–1.0 h) in the test and reference groups, respectively. The terminal elimination half‐lives (t1/2, h) were similar (5.8 and 5.5 h, respectively) indicating that the route of administration did not influence the absorption or elimination of FMS. The systemic clearance (CL, L/h) and the volume of distribution at steady‐state (Vdss, L) were 331.3 ± 444.5 L/h and 403.3 ± 710.4 L following oral administration and 39.1 ± 5.3 L/h and 42.4 ± 25.5 L following IV administration. The absolute bioavailability of the FMS tablet was 18.6%.